Pengaruh Posisi Trendelenburg dengan Posisi Supine terhadap Hipotensi Pasca Spinal Anestesi di RS Bhayangkara TK III Padang - Singgih Elva Putra; Magenda Bisma Yudha; Rahmayana Nova H (Universitas Muhammadiyah Manado, 2025)
Hypotension is the most common complication following spinal anesthesia due to sympathetic nerve blockade, which leads to vasodilation and decreased venous return. One of the preventive measures is patient positioning, such as Trendelenburg and supine positions. This study aimed to determine the effect of both positions on the incidence of post-spinal hypotension at Bhayangkara Hospital TK III Padang. This research applied a quantitative observational analytic design involving 55 elective surgical patients, consisting of Trendelenburg position (n=32) and supine position (n=23). Data were collected through direct observation and blood pressure measurement using NIBP. Data analysis included univariate, bivariate with Spearman Rank test, and Mann-Whitney U test. The results showed that most respondents were female (60%) and classified as ASA I (56.4%). Post-spinal hypotension occurred in 41.8% of patients with systolic <90 mmHg, 27.3% with diastolic <60 mmHg, and 30.9% with a ≥20% decrease from baseline. Bivariate analysis revealed a significant association between patient position and hypotension (p<0.001; rho=0.466). The Mann-Whitney U test showed a significant increase in blood pressure in both positions (p<0.001), but the Trendelenburg position was more protective compared to supine. In conclusion, patient position has a significant effect on the incidence of hypotension after spinal anesthesia. The Trendelenburg position is more effective in preventing hypotension than the supine position, making it a valuable clinical consideration in anesthetic practice.